DIPLOMASI EKONOMI INDONESIA DALAM PENINGKATAN EKSPOR KOPI KE MESIR SELAMA PANDEMI COVID-19 PERIODE 2020 - 2021 - Carissa Putri, (2023)
Coffee is one of Indonesia's leading export products. In 2018, President Jokowi encouraged the expansion of Indonesia's export market to non-traditional markets. Egypt is one of the targets for palm oil and coffee commodities. Through economic diplomacy efforts, Indonesia wants to expand its share of trade in Egypt and strengthen diplomatic relations with Egypt. The existence of the COVID-19 pandemic has hampered international economic activity with its various policies. However, Indonesian coffee export activities to Egypt experienced a rapid increase during the pandemic. Thus, a more in-depth analysis is needed regarding Indonesia's economic diplomacy activities toward Egypt which were carried out during the 2020 - 2021 period. This research aims to analyze and understand the Indonesian government's economic diplomacy strategy toward increasing Indonesian coffee exports to Egypt during the pandemic. The concepts and theories used are economic diplomacy and competitive advantage. The research method used is an interview along with a literature study. This study found that Indonesia uses commercial and trade diplomacy more often. Various promotional and educational activities were carried out to spread knowledge about Indonesian coffee to the people of Egypt. The domino effect resulting from the economic diplomacy of the Indonesian government to Egypt is that more and more Egyptian business people are introducing Indonesian coffee through various domestic coffee festivals. Increasing the performance of coffee exports as one of Indonesia's national interests has finally been achieved.